Freqüência de anticorpos anti-Cysticercus cellulosae em indivíduos de cinco municípios da região Norte do Estado do Paraná - Brasil Frequency of anti-Cysticercus cellulosae antibodies in individuals from five counties in the southern region of Brazil - Maria Valdrinez C. Lonardoni; Dennis A. Bertolini; Thaís G. V. Silveira; Sandra M. A. A. Arraes; Terezinha I. E. Svidzinski; Rosilene F. Cardoso; Mônica L. Gomes; Maria Luiza G. G. Dias; Jeane E. L. Visentainer; Noriko M. Misuta; Miria Ramos; Vera L. D. Siqueira (Universidade de São Paulo, 1996)
Realizou-se inquérito sorológico e epidemiológico para cisticercose em indivíduos de cinco municípios da região Norte do Estado do Paraná, Brasil. De 2.180 indivíduos investigados através da reação de imunofluorescência indireta, 69 (3,2%) apresentaram títulos significativos de anticorpos anti-Cysticercus cellulosae. Os percentuais de indivíduos com títulos significativos encontrados em Sarandi (6,6%) e Marialva (4,7%) não diferem estatisticamente (Z=1.319, P=0,0936), mas diferem dos percentuais encontrados em Mandaguaçu, Paiçandu e Maringá (P<0,01). Destes indivíduos, 47,9% estavam na faixa etária de 21 a 49 anos e 79,4% eram do sexo feminino. Foi comum o relato de queixas como "dores de cabeça" (70,6%), "tonturas" (57,4%) e "convulsões" (7,4%), além de história de teníase (22,1%) e hábitos de ingestão de carne crua bovina (41,2%) ou suína (27,9%) e carne com "canjiquinha" (25,0%). An epidemiological and serological study was carried out on a sample of 2,180 individuals, in five counties in the north of Paraná State - Brazil, using the indirect immunofluorescence test to detect anti-Cysticercus cellulosae antibodies. These individuals, 69 (3.2%) showed significant titers of antibodies. No single significant difference between the proportion of reactivity in Sarandi (6.6%) and in Marialva (4.7%) was observed (Z=1,319, P=0,0936), but it was significantly higher than that observed in Mandaguaçu, Paiçandu and Maringá (P<0.01). Of these individuals, 47.9% were within 21-49 years old and 79.4% were of female sex. "Headache" (70.6%), "faintness" (57.4%), and "convulsions" (7.4%) were among the most frequent by reported, moreover, cases of Taenia infections (22.1%) and the custom of eating uncooked beef (41.2%) or pork (27.9%) and meat containing cysticerci (25.0%) were also related.